2020
DOI: 10.1007/s00330-020-07013-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative chest CT analysis in COVID-19 to predict the need for oxygenation support and intubation

Abstract: Objective Lombardy (Italy) was the epicentre of the COVID-19 pandemic in March 2020. The healthcare system suffered from a shortage of ICU beds and oxygenation support devices. In our Institution, most patients received chest CT at admission, only interpreted visually. Given the proven value of quantitative CT analysis (QCT) in the setting of ARDS, we tested QCT as an outcome predictor for COVID-19. Methods We performed a single-centre retrospective study on COVID-19 patients hospitalised from January 25, 2020… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
119
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(144 citation statements)
references
References 34 publications
17
119
1
7
Order By: Relevance
“…Recently, Lessmann et al developed an AI system that accurately identified COVID-19 patients with high diagnostic performance and assigned SS in good agreement with the experienced radiologist 17 . Lanza et al also used computer-aided quantitative analysis of CT images to determine compromised lung volumes and predict the need for oxygenation support and intubation 18 . They found that patients with compromised lung volumes of > 23% were at risk for intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lessmann et al developed an AI system that accurately identified COVID-19 patients with high diagnostic performance and assigned SS in good agreement with the experienced radiologist 17 . Lanza et al also used computer-aided quantitative analysis of CT images to determine compromised lung volumes and predict the need for oxygenation support and intubation 18 . They found that patients with compromised lung volumes of > 23% were at risk for intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach was applied by Colombi et al [ 18 ] and Lanza et al [ 19 ] determining the value of quantifying the extent of well-aerated lung at baseline chest CT in COVID-19 patients. Both groups used an open-source (not deep learning-based) 3D slicer software to quantify the percentage and absolute volume of well aerated lung in SARS-CoV-2 positive patients at baseline CT.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing our results to that from Colombi et al [ 18 ], the deep learning algorithm provided a faster (120 s vs. 270 s) and more accurate segmentation with post-hoc corrections only necessary in 7% of cases (vs. 61 %). Lanza et al [ 19 ] reported a median time for segmentation of 11 min. The automatic chest CT analysis in our study was carried out on a standard PACS workstation of our institution.…”
Section: Discussionmentioning
confidence: 99%
“…The potential prognostic role of CT-based assessment of lung disease extension has been suggested [13][14][15][16]27], and a few studies have included it in combined prognostic models [17][18][19][20]. Colombi et al found a slightly higher increase in AUC (from 0.83 to 0.86) when adding CT disease extension to a clinical model predictive of intensive care unit admission and/or death [17].…”
Section: Both Models Performed Better In Less Severe Patients In Termmentioning
confidence: 99%